2018
DOI: 10.1108/apjba-07-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ethical work behaviour of Malaysian public sector auditors

Abstract: Purpose The purpose of this paper is to investigate factors affecting ethical work behaviour among Malaysian public sector auditors. Based on Hunt and Vitell model, there are four research objectives for this study: to investigate the influence of ethical climate on public sector auditors ethical work behaviour; to examine the effect of professional commitment on ethical work behaviour of public sector auditors; to investigate the effect of corporate ethical values (CEV) on ethical work behaviour of public sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
5
24
0
1
Order By: Relevance
“…The auditor's with high professional commitment tend to intend to blow the audit firm's fraud case. This finding also supports previous empirical research that the strong accountant's professional commitment, a higher tendency of accountant obligation to report fraudulent actions (Hall et al, 2005;Ismail & Yuhanis, 2018;Mansor et al, 2020;Taylor & Curtis, 2010).…”
Section: Professional Commitment and Whistleblowingsupporting
confidence: 90%
See 1 more Smart Citation
“…The auditor's with high professional commitment tend to intend to blow the audit firm's fraud case. This finding also supports previous empirical research that the strong accountant's professional commitment, a higher tendency of accountant obligation to report fraudulent actions (Hall et al, 2005;Ismail & Yuhanis, 2018;Mansor et al, 2020;Taylor & Curtis, 2010).…”
Section: Professional Commitment and Whistleblowingsupporting
confidence: 90%
“…Auditors with high professional commitment will show a willingness to report their peers' mistakes (Mansor et al, 2020). Previous empirical findings state that professional JRAK 11.1 commitment significantly affects public sector auditors' tendency to behave ethically (Ismail & Yuhanis, 2018;Mansor et al, 2020). Thus, the first hypothesis is:…”
Section: Professional Commitment and Whistleblowingmentioning
confidence: 96%
“…Differences in the level of knowledge about something can affect each individual's attitude towards it, and this attitude will affect that person's intentions (Ismail and Yuhanis, 2018). It is the same in the accounting profession, where different levels of knowledge regarding the professional code of ethics, rules, and laws will affect the attitude one chooses to use to judge something, for example in cases of fraud.…”
Section: The Relationship Between Professional Skepticism and Anticipatory Socializationmentioning
confidence: 99%
“…Also, Elçi & Alpkan (2009); Abadiga et al, (2019) and Koskenvuori, Numminen & Suhonen (2019) defined it as a common perception of the accurate ethical behavior and the approach that ethical concerns should be dealt with. Ismail & Yuhanis (2018) reported that it means a combination of employees' perception toward their organization ethical principles.…”
Section: Nursing Administration Department Faculty Of Nursing Cairo University Egyptmentioning
confidence: 99%